Financial Planning for Retirement: A Psychosocial Perspective - Topa, Gabriela; Lunceford, Gregg; Boyatzis, Richard E. (Frontiers in Psychology, 2018)
Retirement is a time of life that has grown ever longer in the developed world, and the number of pensioners has increased accordingly, questioning the strength of Social Security systems and the social safety net in general. Financial Planning for Retirement (FRP) consists of the series of activities involved in the accumulation of wealth to cover needs in the post-retirement stage of life. The negative short-, mid- and long-term consequences of inadequate Financial Planning for Retirement do not only affect individuals, but also their extended families, homes, eventually producing an unwanted impact on the entire society. The Capacity-Willingness- Opportunity Model has been proposed to understand FPR, combined with Intentional Change Theory, a framework for understanding the process, antecedents and consequences of FPR. From this perspective, we propose this promising model, but there are a large number of variables that have not been included that offer novel ways to deepen our understanding of FPR. A focus on each dimension of the model, the role of age and psychosocial variables associated with demographic indicators such as gender, health status, and migration, allow us to provide a proposal of scientific advancement of FPR.